2017
DOI: 10.1177/1744806917726713
|View full text |Cite
|
Sign up to set email alerts
|

Pain vulnerability and DNA methyltransferase 3a involved in the affective dimension of chronic pain

Abstract: Chronic pain with comorbid emotional disorders is a prevalent neurological disease in patients under various pathological conditions, yet patients show considerable difference in their vulnerability to developing chronic pain. Understanding the neurobiological basis underlying this pain vulnerability is essential to develop targeted therapies of higher efficiency in pain treatment of precision medicine. However, this pain vulnerability has not been addressed in preclinical pain research in animals to date. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…This suggests that the underlying mechanism for pain exacerbation induced by inhibition of the G protein-coupled receptor 40/free fatty acid receptor 1 may be associated with naloxone-induced exacerbation of postoperative pain (Nakamoto et al, 2017). Using a chronic pain mouse model, Wang et al (2017) investigated individual variance in two dimensions of pain behaviors: sensory and emotional. Results showed that mice displayed heterogeneous sensitivities in the chronic pain-induced anxiety-and depression-like behaviors of affective pain.…”
Section: Mouse Models Of Chronic Pain and Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the underlying mechanism for pain exacerbation induced by inhibition of the G protein-coupled receptor 40/free fatty acid receptor 1 may be associated with naloxone-induced exacerbation of postoperative pain (Nakamoto et al, 2017). Using a chronic pain mouse model, Wang et al (2017) investigated individual variance in two dimensions of pain behaviors: sensory and emotional. Results showed that mice displayed heterogeneous sensitivities in the chronic pain-induced anxiety-and depression-like behaviors of affective pain.…”
Section: Mouse Models Of Chronic Pain and Stressmentioning
confidence: 99%
“…Results showed that mice displayed heterogeneous sensitivities in the chronic pain-induced anxiety-and depression-like behaviors of affective pain. Additionally, their molecular analyses revealed that the mice with higher vulnerabilities to developing emotional disorders, such as depression and anxiety, also revealed to have lower levels of protein in the amygdala, and more specifically, in the emotion-processing central nucleus (Wang et al, 2017). Their findings suggest that individual vulnerabilities to pain may be ingrained in the emotional aspect of chronic pain and remain consistent in aspects of negative emotions, in which adaptive changes in the role of the changed protein levels in central amygdala may have significant and longterm consequences.…”
Section: Mouse Models Of Chronic Pain and Stressmentioning
confidence: 99%
“…However, in preclinical research using animal models of chronic pain, the affective/emotional component of chronic pain has been much less studied, possibly due to the extended time (ϳ4 weeks) required to induce behaviors of negative emotion (vs minutes to induce sensory pain) in animal models and, importantly, to the large individual variance that often results in nonsignificant changes in comparisons of group averages. Recently, a growing number of preclinical studies have demonstrated that chronic sensory pain can induce anxietyand depression-like behaviors in rodents (Narita et al, 2006; Caspani et al, 2014; Barthas et al, 2015;Wang et al, 2015Wang et al, , 2017Gambeta et al, 2018). Nevertheless, in contrast to well docu-mented clinical reports of individual vulnerability to the development of chronic pain in patients (Denk et al, 2014), pain vulnerability remains severely understudied in pain research on animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic studies produced significant results in this field. In this regard, mice subjected to partial nerve ligation (PNL) exhibit a significant and long-lasting sensitization of sensory pain compared to sham-operated animals, accompanied by minimal individual variance [119]. On the other hand, the assessment of the affective behavior associated with neuropathic conditions disclosed interesting results.…”
Section: Epigenetic Mechanisms and Novel Approaches To Controllingmentioning
confidence: 99%
“…However, results showed that PNL animals were clearly divided into two different groups, vulnerable and resilient to stress. Surprisingly, statistical analysis highlighted no differences between the sham group and PNL stress-resistant mice [119]. Subsequent molecular experiments showed that chronic neuropathy promotes a significant down-regulation of the DNMT3a enzyme isoform in the central nucleus of AM, mainly in vulnerable animals.…”
Section: Epigenetic Mechanisms and Novel Approaches To Controllingmentioning
confidence: 99%